Scaffoldingthe Development ofTeacher Training Degrees: Educational Cooperation in the University Context - Mayka García García; Manuel J. Cotrina García (Universitat Politècnica de València, 2012)
Educational cooperation has pervaded university language since the European Higher Education System was born. A group of teachers involved in Teacher Training Degrees have analyzed the essence and meaning of their cooperative teaching practices through a proposal for collaborative action-research. This project has been an exercise of professional development that has opened up opportunities for collaboration, reflection and joint action, i.e., a support for the development of the new degrees. This paper presents the analysis of the meaning of cooperative practices in higher education, as well as their light and shade, which emerge from our discussions and shared learning.